Persistence of newly prescribed 5-aminosalicylic acid in patients with ulcerative colitis: A nationwide comprehensive database study. - Tatsuya Noda; Kotaro Kuwaki; Munehito Machida; Yasuyuki Okumura; Yuichi Nishioka; Tomoya Myojin; Tomoaki Imamura (PLoS ONE)
The 5-aminosalicylic acid (5-ASA) agents are first-line drugs for ulcerative colitis (UC). However, intolerance as well as other issues have been reported for these drugs, making it difficult to sustain this treatment; accordingly, the persistence of 5-ASA is an important indicator of UC treatment strategy. We aimed to analyze the persistence of 5-ASA in patients with UC in Japan. This was a 1-year, nationwide, population-based cohort study using the National Database of Health Insurance Claims and Specific Health Checkups of Japan. We identified patients who were assigned UC-related disease codes and newly prescribed 5-ASA between April 2015 and September 2019 and specified the number of days until 5-ASA prescriptions were interrupted during a follow-up of up to 365 days. Among the 137 million patients who were covered by the universal health insurance in Japan during the study period, 68,234 eligible patients were identified. The 5-ASA persistence in these patients were 87.2%, 65.6%, and 56.4% after 30, 180, and 365 days, respectively. The 5-ASA persistence by subtype at 365 days was 54.4%, 56.4%, and 57.6% for time-dependent, pH-dependent, and multi-matrix system types, respectively. The 5-ASA persistence rate after 365 days was 65.0% for those under 20 years of age, 51.0% for those 20-39 years old, 57.5% for those 40-64 years old, and 65.5% for those over 64 years of age. This study revealed the 1-year persistence of newly prescribed 5-ASA in patients with UC newly prescribed 5-ASA in Japan, based on a national claims database of more than 100 million individuals.